Miles, Speed and Technology: Traffic Safety under Oligopolistic Insurance - Maria Dementyeva; Erik T. Verhoef (Tinbergen Institute, 2015)
This paper studies road safety and accident externalities when insurance companies have market power, and can influence road users' driving behaviour via insurance premiums. We obtain both welfare and profit maximizing marginal conditions for first- and second-best insurance premiums for monopoly and oligopoly market structures in insurance. The insurance program consists of an insurance premium, and marginal dependencies ("slopes") of that premium on speed and on the own safety technology choice. While a private monopolist internalizes accident externalities up to the point where compensations to users' benefit matches the full (immaterial) costs, in oligopolistic markets insurance firms do not fully internalize accident externalities that their customers impose upon one another. Therefore, non-optimal premiums as well as speed and technology control apply. Analytical results demonstrate how insurance firms' incentives to influence traffic safety deviate from socially optimal incentives.
Keywords: D43; D62; R41; R42; R48; 330; Accident externalities; congestion externalities; traffic regulations; road safety; second-best; market power